Pengembangan Sistem Pendaftaran Siswa Baru Berbasis Web di SMK N 1 Painan - Eggi Mahnedra; Heri Mulyono; Haris Kurniawan (Smart Education, 2026)
Problems in the new student admission process at SMK Negeri 1 Painan are still encountered, one of which is the administrative process that is carried out manually. This causes applicant data management to be less effective, prone to errors, and time-consuming in the selection process up to the announcement stage. In addition, the limitations of the manual system make it difficult for the admission committee to verify documents and prepare reports. Therefore, a web-based information system is needed to manage the processes of registration, selection, journaling, announcement, and re-registration in a more structured, efficient, and accessible manner. The research method used was the Iterative Development method, which is carried out gradually and repeatedly. The research stages consisted of requirements analysis to identify system needs, design to create the interface and workflow, and development to implement the main features such as dashboard, account management, registration form, document verification, announcement of selection results, and reporting. The results of this study show that system testing using the White Box method obtained an average score of 89.27% in the very valid category. Meanwhile, testing using the Black Box method obtained an average score of 94.86% in the very valid category. The practicality test based on the responses of administrators/admission committees reached 97.22% in the very practical category, while user responses (prospective students) reached 94.5% in the very practical category. The conclusion of this study is that the web-based new student admission system developed with the Laravel framework has been tested valid and practical based on white box and black box testing, as well as user evaluations. Thus, the system is feasible to be used as the main tool in the admission process at SMK Negeri 1 Painan because it improves the effectiveness and efficiency of school administration.